2022
DOI: 10.32394/rpzh.2022.0233
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiovascular diseases risk factors in a group of men hospitalized after myocardial infarction

Abstract: Background. Cardiovascular diseases (CVD) due to their large expansion and high mortality represent a serious problem for society. Ischemic heart disease and myocardial infarction is the leading cause of death and morbidity in both men and women in Europe, although is lower in women than in men. Objective. To evaluate the occurrence of cardiovascular risk factors and the impact of selected dietary habits on lipid profile and body mass index in adult men hospitalized after myocardial infarction in the Cardiocen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…Our research has shown an insufficient frequency of consumption of wholegrain cereals, legumes, fruits and vegetables, with differences in the consumption of these products by women and men only regarding legumes and fruits. Similar unhealthy behaviours were also found in the studies by Mikulska et al (36) and Mrazova et al (38).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our research has shown an insufficient frequency of consumption of wholegrain cereals, legumes, fruits and vegetables, with differences in the consumption of these products by women and men only regarding legumes and fruits. Similar unhealthy behaviours were also found in the studies by Mikulska et al (36) and Mrazova et al (38).…”
Section: Discussionsupporting
confidence: 89%
“…Differences in the frequency of consumption of fish by women and men were found. Low consumption of fish was also indicated in studies conducted by Mikulska et al ( 36 ), Mrazowa et al ( 38 ), Krupa-Kotara et al ( 40 ). Meanwhile, as shown by Petermann-Rocha et al, eating fish instead of meat is associated with a lower risk of adverse cardiovascular effects ( 20 ).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation